2013
DOI: 10.7205/milmed-d-12-00273
|View full text |Cite
|
Sign up to set email alerts
|

Building Military Influenza Surveillance Capacity in West Africa

Abstract: Militaries are especially susceptible to operationally important outbreaks of acute respiratory infections such as pandemic and seasonal influenza. In addition, militaries play important roles for State Parties working to meet International Health Regulations 2005, particularly in developing countries. In 2009, the U.S. Naval Medical Research Unit No. 3 joined with the Noguchi Memorial Institute for Medical Research and the armed forces of Ghana, Burkina Faso, and Côte d'Ivoire to create or improve influenza s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Febrile respiratory illness (FRI) results in substantial disease burden in semi-closed environments such as in the households [1] and militaries [2][3][4]. FRI is most commonly caused by viral infections, as observed in military respiratory surveillance programmes in Finland [5], United Kingdom [4,[6][7][8][9], Netherlands [10], France [11,12], South Korea [13][14][15], West Africa [16], Taiwan [17], China [18], Singapore [19][20][21][22][23][24], and the United States [3,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Febrile respiratory illness (FRI) results in substantial disease burden in semi-closed environments such as in the households [1] and militaries [2][3][4]. FRI is most commonly caused by viral infections, as observed in military respiratory surveillance programmes in Finland [5], United Kingdom [4,[6][7][8][9], Netherlands [10], France [11,12], South Korea [13][14][15], West Africa [16], Taiwan [17], China [18], Singapore [19][20][21][22][23][24], and the United States [3,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…We found that experts from federal ministries, reference laboratories, and uniformed services had insights on emerging pathogens. Partnerships across national agencies in Africa, such as militaries, have aided in developing surveillance programs for emerging zoonotic diseases (Witt et al 2011;Kronmann et al 2013). Modelers could approach these experts to refine their models.…”
Section: Discussionmentioning
confidence: 99%
“…The National Influenza Center (NIC) at NMIMR monitors the circulation of influenza viruses in Ghana and provides information to the WHO Global Influenza Surveillance and Response System (GISRS). As part of the Integrated Disease Surveillance and Response (IDSR) system of the GHS and in collaboration with NAMRU-3, 29 sentinel sites were established for influenza virus surveillance in Ghana [15]. The sites, located across the ten regions of Ghana, included eighteen GHS facilities (regional hospitals, municipal hospitals, district hospitals, polyclinics, and health centers) and eleven military medical reception stations (MRS).…”
Section: Study Sitesmentioning
confidence: 99%